155k views
19 votes
Solve
-21 = -9 + 2/3b

User Intekhab
by
5.6k points

1 Answer

8 votes

Final Answer:
b = -18

Steps/Reasons/Explanation:

Question: Solve
-21 = -9 + (2)/(3)b.

Step 1: Simplify
(2)/(3)b to
(2b)/(3).


-21 = -9 + (2b)/(3)

Step 2: Regroup terms.


-21 = (2b)/(3) - 9

Step 3: Add
9 to both sides.


-21 + 9 = (2b)/(3)

Step 4: Simplify
-21 + 9 to
-12.


-12 = (2b)/(3)

Step 5: Multiply both sides by
3.


-12 ×
3 = 2b

Step 6: Simplify
-12 ×
3 to
-36.


-36 = 2b

Step 7: Divide both sides by
2.


-(36)/(2) = b

Step 8: Simplify
-(36)/(2) to
-18.


-18 = b

Step 9: Switch sides.


b = -18

~I hope I helped you :)~

User Yaron Levi
by
5.1k points